Multi-component composite powder for abradable seal coating and preparation method of multi-component composite powder
By converting Ni-based rods into multi-component composite powder and adopting plasma spraying technology, the problems of low utilization rate of Ni-based rods and difficult to control coating quality are solved, and efficient and stable spraying process and excellent coating performance are achieved.
Patent Information
- Application Number
- CN202510329071.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-20
- Publication Date
- 2025-04-18
AI Technical Summary
The existing Ni-based spray rod has low utilization rate, poor process stability, low spray pass rate, and difficult to control the coating quality, resulting in a high rework rate.
The Ni-based rod is converted into multi-component composite powder, and the plasma spraying process is adopted. The powder material has high yield and utilization rate, which can well match the stability of the plasma spraying process.
It improves spraying efficiency and coating quality, enhances the bonding strength and oxidation resistance of the coating, improves wearability, and reduces the rework rate.
Smart Images

Figure CN119839286A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sealing coating material preparation, and in particular to a multi-component composite powder for abradable sealing coating and a preparation method thereof. Background Art
[0002] In order to meet the service performance requirements of low fuel consumption and high thrust-to-weight ratio of aircraft engines, the use of thermal spraying technology to prepare abradable sealing coatings on the surfaces of engine low-pressure turbine sealing housings, turbine discs, sealing rings, sealing grate teeth and other components has become one of the key technologies for controlling the radial clearance between aircraft engine rotors and stators and improving air path sealing. The requirements for engine sealing coating materials are developing towards high temperature corrosion resistance, high-speed airflow erosion resistance, high bonding strength with the substrate, and excellent self-lubrication and abradability.
[0003] The original abradable sealing coating material used was Ni-based spray rods, which were made by mixing Ni, hBN, Al, Si, Cg and other raw materials with a binder and pressing them, and the spraying process used was flame spraying. With the iterative update of spray powder materials and technologies, the problems of low utilization rate and poor process stability of Ni-based rod spray materials have become increasingly prominent. The rods are easily affected by moisture and mold during storage, resulting in bending and deformation. During transportation, handling and spray clamping, the rods are prone to breakage and damage due to their insufficient strength. At the same time, during the spraying process, the front end needs to be truncated and calibrated, and when the spray rod is sprayed to the rear end, the feeding rod is insufficient and needs to be discarded, resulting in a rod utilization rate of only about 40%. During the flame spraying process, the rod material undergoes uneven melting and spraying, which easily leads to large particles of unmelted material on the coating surface. This requires constant manual scraping, and causes inclusions, fine cracks, and even cracks inside the coating. This makes the coating quality difficult to control, with a high rework rate and a one-time spraying pass rate of only about 50%. The coating performance is low, and it is urgent to complete the technical upgrade of the abradable sealing coating materials and processes. Summary of the invention
[0004] In view of this, the present invention aims to provide a multi-component composite powder for abradable sealing coating and a preparation method thereof. The multi-component composite powder provided by the present invention has controllable material composition, good material composite morphology, and can well match the stability of the plasma spraying process.
[0005] In order to achieve the above object, the present invention provides the following technical solutions: One of the technical solutions of the present invention is a multi-component composite powder for abradable sealing coating, wherein the raw materials are 72 to 88 parts of a nickel silicon intermediate, 1 to 10 parts of a graphite material, 1 to 4 parts of aluminum powder, 6 to 18 parts of hexagonal boron nitride and a binder in parts by weight; the binder accounts for 5% to 12% of the total weight of the nickel silicon intermediate, natural graphite or nickel-coated natural graphite, aluminum powder and hexagonal boron nitride; the graphite material is natural graphite or nickel-coated natural graphite; The preparation method of the nickel-silicon intermediate comprises: mixing silicon powder and nickel powder uniformly, and then performing vacuum sintering, crushing, and screening in sequence; The Si content in the NiSi intermediate is 2-5wt%, with Ni being the balance; and the particle size of the NiSi intermediate is 15μm-75μm.
[0006] A second technical solution of the present invention is a method for preparing the multi-component composite powder for the above-mentioned abradable sealing coating, comprising the following steps: The nickel silicon intermediate, the graphite material, the aluminum powder and the hexagonal boron nitride are uniformly mixed and then ball-milled to obtain a mixture; A binder is added to the mixture to carry out granulation, followed by extrusion composite strengthening, drying and sieving to obtain the multi-component composite powder for the abradable sealing coating.
[0007] A third technical solution of the present invention is an application of the above-mentioned multi-component composite powder for abradable sealing coating in the preparation of sealing coating by plasma spraying.
[0008] The present invention discloses the following technical effects: (1) Compared with the traditional Ni-based rods, the multi-component composite powder material for abradable sealing coating provided by the present invention has uniform and controllable powder material composition, good material composite morphology, high powder material yield and utilization rate, can well match the stability of the plasma spraying process, and greatly improves the spraying efficiency and the quality of the sprayed coating. The coating has high bonding strength and appropriate hardness, and has good oxidation resistance and abradability at 700°C. It can be widely used in the gas path sealing of important parts of aircraft engines.
[0009] (2) The preparation method of the present invention is mechanical agglomeration granulation, which has a simple production process, small equipment investment, and can be mass-produced. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0011] Figure 1 This is a microscopic morphology of the multi-component composite powder for the abradable sealing coating prepared in Example 1; Figure 2 This is a microscopic morphology of the multi-component composite powder for the abradable sealing coating prepared in Example 2; Figure 3 This is a microscopic morphology of the multi-component composite powder for the abradable sealing coating prepared in Example 3; Figure 4 This is a microscopic morphology of the composite powder prepared in Comparative Example 1. DETAILED DESCRIPTION
[0012] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0013] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0014] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0015] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0016] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0017] In order to solve the problems of low utilization rate of Ni-based spraying rods, low spraying qualification rate, low spraying quality, etc., the present invention converts Ni-based rods into composite powders, and adopts a powder plasma spraying process with a higher degree of automation, a more stable spraying process, and more convenient equipment maintenance. The powder is heated, melted, accelerated, and deposited on a substrate in a plasma flame flow to prepare a corresponding coating. The powder material has a high yield and utilization rate, the spraying powder feeding amount is precisely controllable, and the powder material system and coating performance both maintain the action mechanism and performance of the original material.
[0018] The first aspect of the present invention provides a multi-component composite powder for an abradable sealing coating. The raw materials are, by weight, 72 to 88 parts of a nickel silicon (NiSi) intermediate, 1 to 10 parts of a graphite material, 1 to 4 parts of aluminum powder (Al), 6 to 18 parts of hexagonal boron nitride (hBN) and a binder; the binder accounts for 5% to 12% of the total weight of the nickel silicon intermediate, the graphite material, the aluminum powder and the hexagonal boron nitride; the graphite material is natural graphite (Cg) or nickel-coated natural graphite (Ni / Cg).
[0019] In a preferred embodiment of the present invention, the method for preparing the nickel-silicon intermediate is: after uniformly mixing silicon powder and nickel powder, vacuum sintering, crushing, and screening are performed in sequence; The Si content in the NiSi intermediate is 2-5wt% (preferably 4wt%), and Ni is the balance; the particle size of the NiSi intermediate is 15μm-75μm. In the present invention, Si and Ni are combined to prepare the NiSi intermediate. The combination of Si and Ni can effectively reduce the adhesion of the nickel metal phase in the coating, avoid adhesion and damage to the blade, and can also improve the strength of the obtained coating in the high temperature environment of the engine.
[0020] In a preferred embodiment of the present invention, the vacuum sintering temperature is 750-800° C. (preferably 780° C.) and the time is 3-5 h (preferably 3 h).
[0021] The reason why the temperature and time of vacuum sintering are set within the above parameter ranges is: Low sintering temperature and short time will cause incomplete diffusion of Si and residual free Si elements in the powder, and the prepared coating will be highly tough and difficult to scrape; high sintering temperature and long time will cause the sintered material to be highly hard and difficult to break, making spray deposition difficult, the coating to be highly hard, and the blades to wear.
[0022] In a preferred embodiment of the present invention, the particle size of the natural graphite is 45 μm to 90 μm, the thickness of the flake is 200 to 900 nm, and the degree of graphitization of the natural graphite is ≥ 95%; the particle size of the nickel-coated natural graphite is 45 μm to 106 μm; and the mass percentage of Ni in the nickel-coated natural graphite is 60% to 75%.
[0023] In a preferred embodiment of the present invention, the method for preparing the nickel-coated natural graphite is as follows: after the natural graphite, nickel sulfate solution and catalyst are uniformly mixed, reacted under a hydrogen atmosphere, and then filtered, washed and dried in sequence; The catalyst is anthraquinone; the concentration of nickel in the nickel sulfate solution is 16-20 g / L; the mass volume ratio of the natural graphite, the nickel sulfate solution and the catalyst is 2 kg:80-100 L:0.5-2 g; the reaction temperature is 120-150° C., the reaction time is 0.6-1.5 h, and the pressure is 2-6 MPa.
[0024] Since the nickel-coated natural graphite of the present invention has a core-shell coating structure, its composition and particle size affect each other. If the particle size of the nickel-coated natural graphite powder is less than 45 μm, its Ni content is relatively high, and the Ni content in the final multi-component composite powder component is relatively high, the coating hardness is high, and the wearable scraping performance is affected; if the particle size of the nickel-coated natural graphite powder is greater than 106 μm, its graphite content is relatively high, and the particle size of the final multi-component composite powder is relatively coarse, which is easy to collapse in the spray flame flow, reducing the deposition and bonding of the coating.
[0025] In a preferred embodiment of the present invention, the particle size of the aluminum powder is 2 μm to 5 μm; The hexagonal boron nitride has a flaky structure, a flaky layer thickness of 200nm-400nm, a particle size of ≤10μm, and a graphitization index of 1-2.
[0026] In a preferred embodiment of the present invention, the binder is polyethylene glycol, acrylate emulsion or water glass.
[0027] A second aspect of the present invention provides a method for preparing the multi-component composite powder for the above-mentioned abradable sealing coating, comprising the following steps: The nickel silicon intermediate, the graphite material, the aluminum powder and the hexagonal boron nitride are uniformly mixed and then ball-milled to obtain a mixture; A binder is added to the mixture to carry out granulation, followed by extrusion composite strengthening, drying and sieving to obtain the multi-component composite powder for the abradable sealing coating.
[0028] In a preferred embodiment of the present invention, the ball milling time is 8h~15h, the rotation speed is 30rpm~60rpm; the drying temperature is 120~200°C, and the drying time is 8h~16h.
[0029] In a preferred embodiment of the present invention, the sieving is performed by sieving with 60 mesh and 325 mesh sieves in sequence to obtain a finished composite powder with a particle size of 45-300 μm, and the -325 mesh fine powder is collected and returned to the previous step for re-granulation. -325 mesh means less than 325 mesh (45 μm).
[0030] A third aspect of the present invention provides an application of the above-mentioned multi-component composite powder for abradable sealing coating in preparing the sealing coating by plasma spraying.
[0031] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.
[0032] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0033] The parameters of the materials used in the embodiment are: (1) The Si content in the NiSi intermediate is 4wt%, and Ni is the balance; the particle size of the NiSi intermediate is 15μm~75μm; (2) The particle size of natural graphite is 45μm~90μm, the thickness of the flake is 200~900nm, and the graphitization degree of natural graphite is ≥95%; (3) The particle size of the nickel-coated natural graphite is 45 μm to 106 μm; the mass percentage of Ni in the nickel-coated natural graphite is 60% to 75%; (4) The particle size of aluminum powder is 2μm~5μm; (5) The structure of hexagonal boron nitride is a lamellar structure with a lamellar thickness of 200nm~400nm, a particle size of ≤10μm, and a graphitization index of 1~2.
[0034] The preparation method of the NiSi intermediate is as follows: after ball-milling and mixing high-purity Si powder and nickel powder evenly, vacuum sintering at 780°C for 3h; after cooling to room temperature, crushing and screening, and taking powder below 200 mesh as the NiSi intermediate.
[0035] The preparation method of nickel-coated natural graphite is as follows: using high-pressure hydrogen reduction technology, 2kg of natural graphite powder (particle size 160~300 mesh), 80L of nickel sulfate solution (nickel concentration in the nickel sulfate solution is 16g / L) and 1g of catalyst anthraquinone are mixed, and the mixture is reacted at a hydrogen pressure of 4Mpa, a stirring rate of 400rpm, a reaction temperature of 140°C, and a coating time of 1h. After the reaction is completed, the nickel-coated natural graphite powder is obtained after filtering, washing, drying and screening.
[0036] Example 1
[0037] A multi-component composite powder for an abradable sealing coating, the preparation method of which is as follows: (1) Ball milling: NiSi intermediate powder, Cg powder, hBN powder, and Al powder are placed in a ball mill barrel at a mass ratio of 85:2:12:1 together with zirconia grinding balls for ball milling. The weight ratio of the materials to the zirconia balls is 3:5, and the volume ratio of the loading volume is controlled to be 60%. The ball milling time is 12 h, and the ball milling speed is 40 rpm.
[0038] (2) Mechanical granulation: The mixed material in step (1) is separated from the material and the zirconium oxide balls with a 30-mesh screen and the mixed material is collected; the mixed material is added into a stirring granulator, and water glass accounting for 6% of the mixed material by weight is added, and the mixed material is stirred and granulated at a stirring speed of 50 rpm and a stirring time of 15 min; the powder after stirring and granulation is continuously loaded into a spiral granulator for extrusion composite strengthening at a spiral extrusion frequency of 40 Hz and a spiral granulation time of 10 min. After stopping, the granulated material is sieved with a 60-mesh screen and the granulated material is collected.
[0039] (3) Drying: The granulated material collected in step (2) is placed in an oven for drying at a temperature of 190° C. for 8 h.
[0040] (4) Screening: The dried material in step (3) was screened with 60-mesh and 325-mesh screens to obtain a finished composite powder with a particle size of 45-300 µm. The -325-mesh fine powder was collected and returned to the spiral granulator in step (2) for re-granulation. The final powder yield was 95%.
[0041] The composite powder prepared in Example 1 has a morphology as shown in FIG. Figure 1 As shown, the powder has a composite particle structure, without scattered fine powder particles, and the powder finished product rate is 95%. The plasma spraying process parameters used for the composite powder are: current 520A, power 35kW, argon 48L / min, hydrogen 8L / min, carrier gas 3L / min, powder feeding rate 45±5g / min, spraying distance 130mm, gun travel rate 6mm / s, coating deposition efficiency 45.2%, and the prepared coating bonding strength 6.3MPa; after the coating is kept at 700℃ for 100h, the coating is intact and has no cracking or peeling; after the coating is water quenched 15 times at 700℃, under visual conditions, the coating surface is intact, no obvious peeling or delamination is observed, and the coating has excellent thermal shock resistance. The hardness of the coating is 11.2 HB; the average oxidation weight gain rate at 700℃ for 100h is 2.98 (g·m -2 / h); the coating and FGH high-temperature alloy blade were ground at 500℃, 350m / s line speed, 50μm / s feed rate and 200μm feed depth, and the feed depth ratio (IDR) was 12.4%.
[0042] Example 2
[0043] The only difference from Example 1 is that the NiSi intermediate powder, Cg powder, hBN powder and Al powder in a mass ratio of 85:2:12:1 are replaced with NiSi intermediate powder, Ni / Cg powder, hBN powder and Al powder in a mass ratio of 82:5:12:1, and the other parameters and steps are the same as those in Example 1.
[0044] The composite powder prepared in Example 2 has a morphology as shown in FIG. Figure 2As shown, the powder has a composite particle structure, no scattered fine powder particles, and the powder yield is 96%. The plasma spraying process parameters used for the powder are: current 520A, power 35kW, argon 48L / min, hydrogen 8L / min, carrier gas 3L / min, powder feeding rate 45±5g / min, spraying distance 130mm, and gun travel rate 6mm / s. The prepared coating can effectively reduce the graphite powder burnout and improve the powder deposition rate. The deposition efficiency can be increased by 25~40% compared with the powder in Example 1; the coating bonding strength is 6.8MPa; the coating is intact and has no cracking and peeling after being kept at 700℃ for 100h; the coating is quenched 20 times at 700℃. Under visual conditions, the coating surface is intact, no obvious peeling or stratification is observed, and the coating has excellent thermal shock resistance. The hardness of the coating is 12.5 HB; the average oxidation weight gain rate at 700℃ for 100h is 2.15 (g·m -2 / h); the coating and FGH high-temperature alloy blade were ground at 500℃, 350m / s line speed, 50μm / s feed rate and 200μm feed depth, and the feed depth ratio (IDR) was 10.9%.
[0045] Example 3
[0046] The only difference from Example 1 is that the NiSi intermediate powder, Cg powder, hBN powder and Al powder in a mass ratio of 85:2:12:1 are replaced by NiSi intermediate powder, Ni / Cg powder, hBN powder and Al powder in a mass ratio of 75:8:15:2, and the other parameters and steps are the same as those in Example 1.
[0047] The composite powder prepared in Example 3 has the following morphology: Figure 3 As shown, the powder has a composite particle structure, no scattered fine powder particles, and the powder yield is 94.5%. The plasma spraying process parameters used for the powder are: current 520A, power 35kW, argon 48L / min, hydrogen 8L / min, carrier gas 3L / min, powder feeding rate 45±5g / min, spraying distance 130mm, gun travel rate 6mm / s, and the prepared coating has a bonding strength of 4.5MPa; the coating is intact and has no cracking or peeling after being kept at 700℃ for 100h; after 12 water quenchings at 700℃, under visual conditions, the coating surface is intact, no obvious peeling or delamination is observed, and the coating has good thermal shock resistance; after the 15th water quenching, the coating will partially crack, fall off and fail.
[0048] Comparative Example 1 The only difference from Example 1 is that the raw materials of the multi-component composite powder are 70 parts of nickel silicon (NiSi) intermediate, 10 parts of natural graphite (Cg), and 20 parts of hexagonal boron nitride (hBN), and the other processes and parameters are the same as those in Example 1.
[0049] The composite powder morphology prepared in Comparative Example 1 is as follows Figure 4 As shown, the powder has a composite particle structure, no scattered fine powder particles, and the powder finished product rate is 90%. The plasma spraying process parameters used for the powder are: current 520A, power 35kW, argon 48L / min, hydrogen 8L / min, carrier gas 3L / min, powder feeding rate 45±5g / min, spraying distance 130mm, gun travel rate 6mm / s, the prepared coating has a bonding strength of 3.9MPa and a hardness of 7.6HB; the coating has cracking marks after being kept at 700℃ for 100h; after 8 water quenchings at 700℃, the coating peels off under visual conditions.
[0050] Comparative Example 2 The only difference from Example 1 is that the raw materials of the multi-component composite powder are 81.6 parts of nickel powder (Ni), 3.4 parts of silicon powder (Si), 2 parts of natural graphite (Cg), 12 parts of hexagonal boron nitride (hBN), and 1 part of aluminum powder (Al), and the other processes and parameters are the same as those in Example 1.
[0051] The yield of the composite powder prepared in Comparative Example 2 is 86.7%. The plasma spraying process parameters used for the powder are: current 520A, power 35kW, argon 48L / min, hydrogen 8L / min, carrier gas 3L / min, powder feeding rate 45±5g / min, spraying distance 130mm, gun travel rate 6mm / s, coating deposition efficiency 25.8%, the prepared coating bonding strength 8.2MPa, hardness 15.4HB; the coating did not crack or peel after being kept at 700℃ for 100h; after 20 water quenchings at 700℃, under visual conditions, the coating surface is intact, no obvious peeling or delamination is observed, and the coating has excellent thermal shock resistance. However, the coating has high hardness, and the blade tip is severely worn and adhered after high-temperature and high-speed grinding and scraping.
[0052] Comparative Example 3 The only difference from Example 2 is that the Ni content in the nickel-coated natural graphite is increased from 70% to 85%, the balance is graphite, the powder particle size of the nickel-coated natural graphite powder is controlled below 45 μm, and the other parameters and steps are the same as Example 2.
[0053] The yield of the composite powder prepared in Example 2 is 92%. The plasma spraying process parameters used for the powder are: current 520A, power 35kW, argon 48L / min, hydrogen 8L / min, carrier gas 3L / min, powder feeding rate 45±5g / min, spraying distance 130mm, and gun travel rate 6mm / s. The prepared coating deposition efficiency is 52.6%, the coating bonding strength is 7.9MPa, and the coating hardness is 14.8HB. After the coating is kept at 700°C for 100h, the coating is intact without cracking and peeling; after the coating is water quenched 20 times at 700°C, under visual conditions, the coating surface is intact, no obvious peeling or delamination is observed, and the coating has excellent thermal shock resistance. The coating and FGH high-temperature alloy blade were ground at 500°C, 350m / s line speed, 50μm / s feed rate and 200μm feed depth, and the feed depth ratio (IDR) was 25.6% (the IDR value of conventional abradable coatings needs to be less than 15%).
[0054] Comparative Example 4 The only difference from Example 2 is that the Ni content in the nickel-coated natural graphite is reduced from 70% to 50%, the remainder is graphite, the particle size of the nickel-coated natural graphite powder is controlled to be above 106 μm, and the other parameters and steps are the same as those in Example 2.
[0055] The yield of the composite powder prepared in Example 2 is 92.5%. The plasma spraying process parameters used for the powder are: current 520A, power 35kW, argon 48L / min, hydrogen 8L / min, carrier gas 3L / min, powder feeding rate 45±5g / min, spraying distance 130mm, and gun travel rate 6mm / s. The prepared coating deposition efficiency is 32.8%, the coating bonding strength is 5.6MPa, and the coating hardness is 12.6HB. After the coating is kept at 700℃ for 100h, the coating is intact without cracking and peeling; after the coating is water quenched 15 times at 700℃, under visual conditions, the coating surface has cracking.
[0056] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A multi-component composite powder for abradable sealing coating, characterized in that: The raw materials are 72 to 88 parts by weight of a nickel silicon intermediate, 1 to 10 parts of a graphite material, 1 to 4 parts of aluminum powder, 6 to 18 parts of hexagonal boron nitride and a binder; the binder accounts for 5% to 12% of the total weight of the nickel silicon intermediate, the graphite material, the aluminum powder and the hexagonal boron nitride; the graphite material is natural graphite or nickel-coated natural graphite; The preparation method of the nickel-silicon intermediate comprises: mixing silicon powder and nickel powder uniformly, and then performing vacuum sintering, crushing, and screening in sequence; The Si content in the NiSi intermediate is 2-5wt%, with Ni being the balance; and the particle size of the NiSi intermediate is 15μm-75μm.
2. The multi-component composite powder for abradable sealing coating according to claim 1, characterized in that: The vacuum sintering temperature is 750-800°C and the time is 3-5h.
3. The multi-component composite powder for abradable sealing coating according to claim 1, characterized in that: The particle size of the natural graphite is 45 μm to 90 μm, the thickness of the flake is 200 to 900 nm, and the graphitization degree of the natural graphite is ≥ 95%; The particle size of the nickel-coated natural graphite is 45 μm to 106 μm; the mass percentage of Ni in the nickel-coated natural graphite is 60% to 75%.
4. The multi-component composite powder for abradable sealing coating according to claim 1 or 3, characterized in that: The method for preparing the nickel-coated natural graphite comprises: uniformly mixing natural graphite, a nickel sulfate solution and a catalyst, reacting the mixture under a hydrogen atmosphere, and then filtering, washing and drying the mixture in sequence.
5. The multi-component composite powder for abradable sealing coating according to claim 4, characterized in that: The catalyst is anthraquinone; the concentration of nickel in the nickel sulfate solution is 16-20 g / L; the mass volume ratio of the natural graphite, the nickel sulfate solution and the catalyst is 2 kg:80-100 L:0.5-2 g; the reaction temperature is 120-150° C., the reaction time is 0.6-1.5 h, and the pressure is 2-6 MPa.
6. The multi-component composite powder for abradable sealing coating according to claim 1, characterized in that: The particle size of the aluminum powder is 2 μm to 5 μm; The hexagonal boron nitride has a flaky structure, a flaky layer thickness of 200nm-400nm, a particle size of ≤10μm, and a graphitization index of 1-2.
7. The multi-component composite powder for abradable sealing coating according to claim 1, characterized in that: The binder is polyethylene glycol, acrylic emulsion or water glass.
8. A method for preparing the multi-component composite powder for abradable sealing coating according to any one of claims 1 to 7, characterized in that: The following steps are involved: The nickel silicon intermediate, the graphite material, the aluminum powder and the hexagonal boron nitride are uniformly mixed and then ball-milled to obtain a mixture; A binder is added to the mixture to perform granulation, followed by extrusion composite strengthening, drying and sieving to obtain the multi-component composite powder for the abradable sealing coating.
9. The method for preparing a multi-component composite powder for an abradable sealing coating according to claim 8, characterized in that: The ball milling time is 8h~15h, the rotation speed is 30rpm~60rpm; the drying temperature is 120~200℃, and the time is 8h~16h.
10. Use of the multi-component composite powder for abradable sealing coating according to any one of claims 1 to 7 in preparing sealing coating by plasma spraying.
Citation Information
Patent Citations
Wearable composite powder for sealing, coating and preparation methods
CN102168239A
Method for preparing thermal spraying obturating coating material
CN102168240A
Low-burning-loss abrasive coating material and application thereof
CN110872677A
Nickel silicon or boron nitride abradable sealing coating and preparation method thereof
CN117488232A
High-temperature-wear-resistant laser cladding copper-based composite coating and preparation method thereof
CN118726970A